Effects of foliar application of zinc sulfate on growth, yield and essential oil of Perilla (Perilla frutescens L.) and holy basil (Ocimum sanctum L.) - Minh Dung Ha-Tran; Quyen Cuoc Le; Minh Nhut Nguyen; Van Thinh Tran; Thi Thuy Lieu Nguyen (CTU Journal of Innovation and Sustainable Development, 2025)
This study was conducted on gray soil at the research station of the Faculty of Agronomy, Nong Lam University - Ho Chi Minh City, Viet Nam. The objective of the study was to investigate the effects of foliar zinc sulfate application on perilla and holy basil cultivation. For perilla, several morphological characteristics, including plant height, stem diameter, leaf length, leaf width, and leaf number on the main stem, showed statistically significant differences between the control and the 2.0 g/L ZnSO4.7H2O treatment. In contrast, only plant height in holy basil was significantly affected by ZnSO4.7H2O spray at 30 days after cutting. Regarding other physiological traits, both perilla and holy basil were able to maintain high levels of chlorophyll, carotenoid, total protein, and essential oil content. These findings suggest that zinc supplementation via foliar nutrition is a promising approach to improve not only agricultural yield but also the economic efficiency of medicinal plant cultivation.